Diagnostic and prognostic role of urinary collagens in primary human bladder cancer - Miyake, Makito; Morizawa, Yosuke; Hori, Shunta; Tatsumi, Yoshihiro; Onishi, Sayuri; Owari, Takuya; Iida, Kota; Onishi, Kenta; Gotoh, Daisuke; Nakai, Yasushi; Anai, Satoshi; Chihara, Yoshitomo; et al. (Cancer science, 2017)
Collagen type 4 alpha 1 (COL4A1) and collagen type 13 alpha 1 (COL13A1) produced by urothelial cancer cells support the vital oncogenic property of tumor invasion. We investigated the diagnostic and prognostic capability of COL4A1 and COL13A1 in voided urine and compared the observed values with those of fragments of cytokeratin‐19 (CYFRA21‐1), nuclear matrix protein 22 (NMP‐22), and voided urine cytology in bladder cancer (BCa). We collected voided urine samples from 154 patients newly diagnosed with BCa, before surgery and from 61 control subjects. Protein levels of COL4A1, COL13A1, CYFRA21‐1, and NMP‐22 in urine supernatants were measured using enzyme‐linked immunosorbent assays. Diagnostic performance and optimal cut‐off values were determined by receiver operating characteristic analysis. Urine levels of COL4A1, COL13A1, the combined values of COL4A1 and COL13A1 (COL4A1 + COL13A1), and CYFRA21‐1 were significantly elevated in urine from patients with BCa compared to the controls. Among these biomarkers, the optimal cut‐off value of COL4A1 + COL13A1 at 1.33 ng/mL resulted in 57.4%, 83.7%, 56.1%, 80.7%, and 91.7% sensitivity for low‐grade tumors, high‐grade tumors, Ta, T1, and muscle invasive disease, respectively. We evaluated the prognostic value of preoperative urine levels in 130 non‐muscle invasive BCa samples after the initial transurethral surgery. A high urinary COL4A1 + COL13A1 was found to be an independent risk factor for intravesical recurrence. Although these data need to be externally validated, urinary COL4A1 and COL13A1 could be a potential diagnostic and prognostic biomarker for BCa. This easy‐to‐use urinary signature identifies a subgroup of patients with a high probability of recurrence and progression in non‐muscle invasive and muscle invasive BCa. This study demonstrated the diagnostic and prognostic performance of urinary collagens in comparison with those of CYFRA21‐1, NMP‐22, and voided urine cytology in bladder cancer. This easy‐to‐use urinary signature identifies a subgroup of patients with high probability of recurrence and progression in non‐muscle invasive disease..